N-Iodoacetyl-d-glucosamine, an inhibitor of growth and glycoside uptake in Escherichia coli - Kent, P. W. (1970)
1. Synthesis of N-iodoacetyl-d-glucosamine and its N-iodo[1,2-(14)C(2)]acetyl form has been achieved from the tetra-O-acetyl amino sugar and iodoacetic acid in the presence of dicyclohexylcarbodi-imide followed by catalytic deacetylation. 2. N-Iodoacetylglucosamine (up to 0.1mm) linearly inhibits uptake (up to 1min) of methyl α-d-glucoside by Escherichia coli ML308 and K12. Uptake of methyl β-d-thiogalactoside and glycerol is also inhibited. 3. Growth of the organism (strain ML308) on glucose, succinate and glycerol is strongly inhibited by the iodoacetyl compound. The inhibition is relieved by N-acetylglucosamine. 4. The inhibitor has multiple effects, some of which are considered to be intracellular. 5. A separate transport pathway exists for N-acetylglucosamine by means of which the iodoacetyl analogue may enter the cell.